Uterine prolapse in cows: Effect of raising the rear end on the clinical outcomes and reproductive performance - M. Ishii; T. Aoki; K. Yamakawa; T. Uyama; S. El-khodery; M. Matsui; Y. Miyake (Veterinární Medicína, 2010)
The aim of this study was to evaluate the effect of raising the rear end when replacing the prolapsed uterus in cows on the outcome and reproductive performance. A total of 76 cows with uterine prolapse were investigated, 10 of which had died before treatment. According to the posture, cows were divided into standing (Standing: n = 11) and recumbent (Recumbent: n = 55). Recumbent cows were subdivided randomly into lying (Lying: n = 24), lifting up using a cow-lift (Cow-lift: n = 18), and raising hind legs using a tractor (Raising: n = 13). Recovery rate after treatment of all cows was 60.6%. The recovery rate of Recumbent (52.7%) was significantly (P < 0.01) lower than Standing (100%). Among the recumbent cows, Lying showed the lowest recovery rate (37.5%), which was significantly lower than the recovery rate (64.5%) of the combined Cow-lift and Raising groups. The mean nonpregnant term of Raising (144 days) was significantly (P < 0.05) shorter than of Cow-lift (297 days). In conclusion, the method of replacing the uterus by raising the hind legs during treatment of uterine prolapse in cows could improve the recovery rate and breeding performance.